2017
DOI: 10.1007/s00784-017-2282-0
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT evaluation of voids using two root filling techniques in the placement of MTA in mesial root canals of Vertucci type II configuration

Abstract: Warm vertical compaction and ultrasonically activated MTA fillings revealed similar quality at the isthmus area, which was superior to manually compacted MTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…The use of extracted human teeth sharing similar anatomy might mimic clinical set up accurately; however, recruitment of the specimens should be performed meticulously due to the high variation of isthmus type, volume, length, and dimensions. Micro‐CT enables the validation of experimental groups' homogeneity prior to experimental procedures without harming the specimens (Keleş et al, ). Isthmus dimensions were taken into consideration to create homogeneity by selecting similar specimens regarding their length, major diameters, and volume in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of extracted human teeth sharing similar anatomy might mimic clinical set up accurately; however, recruitment of the specimens should be performed meticulously due to the high variation of isthmus type, volume, length, and dimensions. Micro‐CT enables the validation of experimental groups' homogeneity prior to experimental procedures without harming the specimens (Keleş et al, ). Isthmus dimensions were taken into consideration to create homogeneity by selecting similar specimens regarding their length, major diameters, and volume in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that the mean percentage of void volume was 1.4 and 2.3% at the apical 3 mm of root canals of teeth showing Vertucci Type II canal morphology and a V‐shaped isthmus, irrespective of filling techniques (Keleş et al, ). It is known that isthmus ovality is an important factor for the void distribution produced by root canal filling techniques (Çelikten et al, 2016; Keleş et al, ). Keleş et al () reported that canal filling techniques resulted in void percentages between 2.6 and 10% in the coronal half of canals, where the ovality is the most increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of microorganisms in these areas compromises the endodontic treatment outcome, as this is a risk factor for post-treatment apical periodontitis [ 9 ]. Therefore, the significance of a 3-dimensional (3D) sealing of the root canal system must be emphasized [ 10 ].…”
Section: Introductionmentioning
confidence: 99%